Tissue fibrosis and its correlation with malignancy in canine mammary tumors - Toledo, Gabriela N. [UNESP]; Feliciano, Marcus A.R. [UNESP]; Uscategui, Ricardo A.R. [UNESP]; Magalhães, Geórgia M.; Madruga, Gabriela M. [UNESP]; Vicente, Wilter R.R. [UNESP] (Universidad de Antioquia, 2018)
Background: Fibrosis is present in several pathologies associated with mammary carcinogenesis. Objective: To evaluate and quantify the fibrosis present in malignant and benign mammary neoplasms in bitches. Methods: Eighty-three samples were divided according to histopathological diagnosis into benign (n= 21) and malignant (n= 62) neoplasms. Haematoxylin-eosin and Masson’s trichrome were used to locate the connective tissue, and the extent of fibrosis was assessed with image software. Results: Benign neoplasms were classified into adenomas (cystic, complex, and tubular), benign mixed tumor, and ductal and lobular hyperplasia. Malignant neoplasms were classified as carcinomas (complex, mixed tumor, in situ tubular, tubulopapillary, and solid). Grade I was the most prevalent histopathological class, followed by grade II and III. Fibrosis was classified as severe, moderate, or discrete. No significant (p>0.05) difference was observed for the percentage of fibrosis between malignant and benign group neoplasms. However, difference (p=0.028) was found for fibrosis percentage between histopathological subtypes of tumors. The benign subtype of lobular hyperplasia presented differences between cystic adenoma and benign mixed tumor. The in situ malignant tubular carcinoma subtype presented differences between solid and tubulopapillary carcinoma. Conclusions: Fibrosis in canine mammary tumors can be estimated with Massons’s trichrome staining.
Fibrosis tisular y su correlación con malignidad en neoplasias mamarias caninas
Fibrose tecidual e sua correlação com a malignidade em neoplasias mamárias em cadelas
Keywords: Biological biomarkers; Breast cancer; Dogs; Histological stain; Histopathology; Masson’s trichrome